Don't blame the tools : the adoption and implementation of managerial innovations - Daniel, Elizabeth, 1962- (Elsevier/Cima Pub., 2009)
Those managing organisations are often criticised for being 'faddish' in their use of new management ideas or innovations, too easily falling into the trap of adopting the latest new idea or concept because it is 'flavour of the month'. This research-based report presents an in-depth account and analysis of the adoption and implementation of two popular large-scale managerial innovations in four different organisations. It provides case studies of actual adoption and implementation of the balanced scorecard and programme/project management offices. The study explores the reasons for the adoption of the innovations and how these reasons shape implementation success. The report also provides examples of good practice that practising managers use to improve the implementation of new management practices in their own organisations. . Presents an original research-based study that explores the reasons why organisations adopt new management practices (e.g. balanced scorecard and programme/project management offices) . Links the reasons for adoption with the success of implementation . Provides examples of good practice that can improve the implementation of new management practices in organisations.